Accountability audits of natural resources and industrial green total factor productivity: evidence from China - Rongbing Huang; Xiaomin Zou (Humanities & Social Sciences Communications)
Abstract Accountability audits of natural resources, which aim to support green development, constitute a Chinese institutional innovation. In this study, we employed a multiperiod difference-in-differences model to investigate the influence of accountability audits of natural resources on the industrial green total factor productivity by matching 2012 to 2019 province‒industry annual data. We demonstrated that accountability audits of natural resources considerably increase the green total factor productivity among heavily polluting industries and the overall industry greening level. These findings continued to hold after expansion tests, and a series of robustness tests were performed. Further analysis revealed that via resource allocation optimization and driven by technological innovation, audit supervision supports increased green total factor productivity levels among heavy polluters. Moreover, regional, industrial, and individual characteristics exerted heterogeneous impacts on industrial green transformation. Thus, this study yields a novel contribution, as it is the first in which industry-level data are used to clarify the controversy observed in previous studies and the first to provide incremental empirical evidence to support the reliability and sustainability of the policy effects of accountability audits of natural resources.